2018
DOI: 10.1016/j.scitotenv.2017.08.047
|View full text |Cite
|
Sign up to set email alerts
|

Effects of agricultural land use on fluvial carbon dioxide, methane and nitrous oxide concentrations in a large European river, the Meuse (Belgium)

Abstract: • Large data-set of CO 2 , CH 4 , and N 2 O in the surface waters of the Meuse River We report a data-set of CO 2 , CH 4 , and N 2 O concentrations in the surface waters of the Meuse river network in Belgium, obtained during four surveys covering 50 stations (summer 2013 and late winter 2013, 2014 and 2015), from yearly cycles in four rivers of variable size and catchment land cover, and from 111 groundwater samples. Surface waters of the Meuse river network were over-saturated in CO 2 , CH 4 , N 2 O with resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
112
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(131 citation statements)
references
References 67 publications
19
112
0
Order By: Relevance
“…The two estuaries with considerably higher CH 4 surface concentrations, Guanabara Bay and Pearl River estuaries, also have a history of extremely high anthropogenic inputs (Chen et al a ; Cotovicz et al ). CH 4 surface concentrations were greater, on average, in tributaries than in other sites, corroborating high values reported in small rivers and streams (Butman and Raymond ; McGinnis et al ; Sawakuchi et al ), especially those impacted directly by wastewater or agricultural inputs (Rajkumar et al ; Garnier et al ; Borges et al ; Drake et al ).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The two estuaries with considerably higher CH 4 surface concentrations, Guanabara Bay and Pearl River estuaries, also have a history of extremely high anthropogenic inputs (Chen et al a ; Cotovicz et al ). CH 4 surface concentrations were greater, on average, in tributaries than in other sites, corroborating high values reported in small rivers and streams (Butman and Raymond ; McGinnis et al ; Sawakuchi et al ), especially those impacted directly by wastewater or agricultural inputs (Rajkumar et al ; Garnier et al ; Borges et al ; Drake et al ).…”
Section: Discussionsupporting
confidence: 78%
“…The reasons for the difference in p CO 2 patterns observed between Raymond et al () and our own data may be explained by the relatively lower river flow (50% compared to our study) during the Raymond et al () study (USGS, accessed April 2018, https://waterdata.usgs.gov/nwis/uv?site_no=01358000). Lower river flow would increase water residence time—increasing sedimentation of organic matter, enhancing heterotrophy (Crawford et al ), and biogeochemical transformations, as well as facilitating the accumulation of GHGs (Raymond et al ; Borges et al ).…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted by Beaulieu et al () on 12 headwater streams in Kalamazoo basin in Michigan, USA, N 2 O concentrations were highest in agricultural streams. Schade et al () also found higher N 2 O fluxes in a stream that drained an organic dairy farm in New Hampshire, USA, while Borges et al () found similar results for streams draining agricultural and pasture lands in the Meuse River. These studies further highlighting the influence of land use on N 2 O fluxes and the potential for hotspots related to either agricultural or animal influence, presumably because of N and organic matter inputs.…”
Section: Introductionmentioning
confidence: 81%
“…Predicted increased terrestrial N use is therefore expected to cause global estuarine emissions to triple (Kroeze et al, 2005). The effect of N inputs and/or land use intensity on estuary N 2 O dynamics are yet to be directly measured, but anecdotal evidence shows high N 2 O fluxes from aquatic environments surrounded by intensive agricultural (Borges et al, 2018;Lin et al, 2016) and low/negative fluxes from those surrounded by more "pristine" woodlands (Liu et al, 2015;Maher et al, 2016). However, the knowledge that N cycling is highly sensitive to changes in N loads (Mulholland et al, 2008) and benthic habitat health (Eyre et al, 2016) necessitates a careful evaluation of whether N 2 O emissions will respond linearly to these increases in land use intensity.…”
Section: Citationmentioning
confidence: 99%